Theoretical investigation of penicillamine adsorption on mg12o12 fullerene-like cages considering solvent effects, electronic properties, and potential biomedical applications - Hadil Faris Alotaibi; Anjan Kumar; Yashwantsinh Jadeja; Suhas Ballal; Shaker Al-Hasnaawei; Abhayveer Singh; T. Krithiga; Subhashree Ray; Kamal Kant Joshi (Scientific Reports)
Abstract This study explores the enhancement of adsorption properties of penicillamine (PCA) in both neutral and zwitterionic forms through the use of magnesium oxide (Mg12O12) fullerene-like cages, supported by density functional theory (DFT) and molecular dynamics (MD) simulations. Results indicate that PCA adsorption is spontaneous and exothermic, with the cage preferentially abstracting a hydrogen atom from surface hydroxyl groups, leading to strong interactions evidenced by adsorption energies of -2.250 eV in water and − 2.204 eV in chloroform. Charge transfer from the Mg12O12 cage to PCA was approximately 0.299 |e| in water and 0.278 |e| in chloroform, resulting in decreased global hardness and increased chemical potential of the complex, suggesting enhanced reactivity. During the adsorption process, PCA in zwitterionic form exhibited the highest increase in dipole moment, with a value of 12.540 Debye (complex F), compared to the neutral form with the value of 11.382 (complex C) Debye, suggesting enhanced solubility of the system. Dynamic simulations showed that binding energies fluctuate and reach equilibrium after 120 ps. Time-dependent DFT analyses revealed solvent-dependent effects on exciton stability and absorption spectra: water stabilizes charges and enhances absorption, while chloroform induces peak broadening and redshift due to Coulomb interactions. Infrared spectroscopy demonstrated significant spectral shifts upon PCA adsorption, particularly via its carboxyl group, which exhibited the lowest energy gap (Eg) and favorable electronic interactions. Our findings suggest that Mg12O12 cages hold significant potential as biosensors and delivery vehicles for penicillamine, with solvent environment playing a crucial role in adsorption characteristics.